An analysis of educational games design frameworks from software engineering perspective - Ahmad, Mifrah; Ab Rahim, Lukman; Arshad, Noreen Izza (Universiti Utara Malaysia Press, 2015)
Game-based learning has dominantly embedded itself into a tool of education in the 21st century. In developing educational games, many researchers have proposed frameworks to defi ne elements of an educational game. This paper presents a survey of the different frameworks for educational games and analyzes these frameworks against several criteria for effective video games, well-designed games and key elements of educational games. The authors will also look at the frameworks support towards learning theories. In addition, the analysis continues in the context of software engineering practices to develop effective educational games.